The request [large type] - Bell, David, 1969 November 17- (Thorndike Press large print mystery, 2021)
"Ryan Francis has it all-great job, wonderful wife, beautiful child-and he loves posting photos of his perfect life on social media. Until the night his friend Blake asks him to break into a woman's home to retrieve incriminating items that implicate Blake in an affair. Ryan refuses to help, but when Blake threatens to reveal Ryan's darkest secret-which could jeopardize everything in Ryan's life-Ryan has no choice but to honor Blake's request. When he arrives at the woman's home, Ryan is shocked to find her dead-and just as shocked to realize he knows her. Then his phone chimes, revealing a Facebook friend request from the woman. With police sirens rapidly approaching, Ryan flees, wondering why his friend was setting him up for murder. Determined to keep his life intact and to clear his name, Ryan must find the real murderer-but solving the crime may lead him closer to home than he ever could have imagined"--